The experiences of Malaysian in industrialised building system (IBS) to enhance construct ability and sustainability in construction project - Mohd Nawi, Mohd Nasrun (UUM College of Business, 2011)
The reality of construction is that most of the problems encountered in the field such as reworks, delay and low in quality or productivity are often compounded by inherent design flaws that generated in the design phase.Implementing construct ability concept is an alternative solution to overcome the problem.Construct ability is often portrayed as integrating construction knowledge, resource, technology and experience into the engineering and design of a project.Since 1998, Malaysian government through Construction Industry Development Board seriously took an action to reform the current construction practice (currently use conventional method) towards industrialization concept.One of the main strategies been taken by the government which introduced a concept of design of prefabrication, pre-assembly and modularization especially in public projects.This paper will highlight the initiative be done by in the Malaysian construction industry to implement that system and indirectly the concept of construct ability will be enhanced.